17O MRS assesses the effect of mild hypothermia on oxygen consumption rate in tumors. (21st April 2017) - Neveu, Marie‐Aline; Joudiou, Nicolas; De Preter, Géraldine; Dehoux, Jean‐Paul; Jordan, Bénédicte F.; Gallez, Bernard
Abstract : Although oxygen consumption is a key factor in metabolic phenotyping, its assessment in tumors remains critical, as current technologies generally display poor specificity. The objectives of this study were to explore the feasibility of direct 17 O nuclear magnetic resonance (NMR) spectroscopy to assess oxygen metabolism in tumors and its modulations. To investigate the impact of hypometabolism induction in the murine fibrosarcoma FSAII tumor model, we monitored the oxygen consumption of normothermic (37°C) and hypothermic (32°C) tumor‐bearing mice. Hypothermic animals showed an increase in tumor p O2 (measured by electron paramagnetic resonance oximetry) contrary to normothermic animals. This was related to a decrease in oxygen consumption rate (assessed using 17 O magnetic resonance spectroscopy (MRS) after the inhalation of 17 O2 ‐enriched gas). This study highlights the ability of direct 17 O MRS to measure oxygen metabolism in tumors and modulations of tumor oxygen consumption rate. Abstract : Tumor oxygenation (measured by electron paramagnetic resonance oximetry) and O2 consumption rate (measured by monitoring the dynamic changes in the H2 17 O signal using nuclear magnetic resonance spectroscopy after inhalation of 17 O2 ‐enriched gas) were studied in normothermic and hypothermic tumor‐bearing mice. Hypothermic animals showed an increase in tumor p O2 contrarily to normothermic animals that was related to a decrease in oxygen consumption rate. This study highlights the ability of direct 17 O MRS to measure oxygen metabolism in tumors and modulations of tumor oxygen consumption rate.